1981
DOI: 10.1111/j.1365-2362.1981.tb01844.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin‐ll blockade on systemic and hepatic haemodynamics and on the renin‐angiotensin‐aldosterone system in cirrhosis with ascites

Abstract: We have studied the effect of angiotensin-II blockade with saralasin on the cardiovascular and hepatic hemodynamics and on the renin-angiotensin-aldosterone system in fourteen patients with cirrhosis and ascites. Control measurements showed that most of the patients had a low mean arterial pressure, high plasma volume, normal or high cardiac index, low peripheral resistance and high plasma renin activity and aldosterone concentration. The wedged hepatic venous pressure was increased in each patient and the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(46 citation statements)
references
References 34 publications
1
44
1
Order By: Relevance
“…24 The significant decrease in total bilirubin that occurred during losartan treatment in the group with severe portal hypertension cannot be explained from our data and requires further investigation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…24 The significant decrease in total bilirubin that occurred during losartan treatment in the group with severe portal hypertension cannot be explained from our data and requires further investigation.…”
Section: Discussionmentioning
confidence: 69%
“…[14][15][16]23 In the early 1980s, it was demonstrated that intravenous administration of saralasin, a competitive peptide angiotensin II antagonist with intrinsic agonist activity, reduces elevated portal pressure in cirrhosis. 24 However, because of its short duration of action and poor oral bioavailability, saralasin is not suitable for long-term treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhotic patients have a cardiovascular disturbance characterized by low arterial pressure, high cardiac output, and increased plasma volume (1)(2)(3)(4). Besides arteriolar vasodilation and arteriovenous shunting, these patients exhibit a diminished sensitivity to pressor hormones and impaired hypoxic vasoconstriction (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30% of patients with cirrhosis and ascites have normal levels of plasma renin activity and aldosterone. These patients have a better survival compared to patients with abnormal values of these parameters [5,9,13]. Patients with increased plasma renin activity and increased aldosterone and norepinephrine levels also have a high probability of developing HRS [14,15].…”
Section: Circulatory Functionmentioning
confidence: 97%
“…The severities of renal and circulatory dysfunction are well established prognostic factors in patients with cirrhosis and ascites. In fact sodium retention, a highly prevalent renal function abnormality of cirrhosis, is associated with reduced survival [13]. Sodium excretion should ideally be measured in patients on a low-sodium diet of 70-90 mEq/day during 5-7 days and off diuretics.…”
Section: Renal Functionmentioning
confidence: 99%